Agglomeration bonus and endogenous group formation. Issue 1 (8th February 2022) - Bareille, François; Zavalloni, Matteo; Viaggi, Davide
Abstract: Agglomeration bonus schemes are envisioned to incentivize the connectivity of habitat conservation across landowners. Assuming full cooperation among landowners at the landscape scale, the bulk of the literature theoretically finds that agglomeration bonus schemes are more cost effective in achieving biodiversity conservation than spatially homogenous payments. However, it may be rational for landowners not to cooperate all together but, rather, to cooperate within smaller groups. Here, we analyze the cost effectiveness of agglomeration bonus schemes when such partial cooperation is allowed, that is, when cooperation is endogenously chosen. We introduce a spatially explicit ecological‐economic model within a coalition formation game to assess how landowners form stable coalition structures and how this affects biodiversity conservation under a wide range of (i) degrees of spatial cost autocorrelation, (ii) bonuses and flat‐rate payments, (iii) species dispersal rates, and (iv) coordination costs. We find that agglomeration bonus schemes are more cost effective than homogenous payments only for low public expenditures. This condition is not identified if full cooperation is assumed. We find, however, that full cooperation never emerges and hence that such an assumption leads to an overestimation of the cost effectiveness of agglomeration bonus schemes. Moreover, we find that the cost effectiveness of agglomeration bonus schemes increases when the spatial cost autocorrelation and species dispersal rate decrease. Finally, coordination costs do not affect the cost effectiveness of the agglomeration bonus scheme but they have implications for its design because of their impact on coalition formation.